Cancer-Associated Fibroblasts Promote Migration and Invasion of Non-Small Cell Lung Cancer Cells via miR-101-3p Mediated VEGFA Secretion and AKT/eNOS Pathway - Guo, Xueru; Chen, Mengmeng; Cao, Limin; Hu, Yiming; Li, Xueqin; Zhang, Qicheng; Ren, Yinghui; Wu, Xiang; Meng, Zhaowei; Xu, Ke (Frontiers in Cell and Developmental Biology, 2021)
Cancer-associated fibroblasts (CAFs) are major component of tumor microenvironment (TME), which plays crucial roles in tumor growth, invasion and metastasis; however, the underling mechanism is not fully elucidated. Despite many studies are focused on the tumor promoting effect of CAFs-derived cytokines, the upstream regulators of cytokine release in CAFs is largely unknown. Here we found that miR-101-3p was downregulated in primary lung cancer-associated CAFs compared to normal fibroblasts (NFs). Ectopic overexpression of miR-101-3p suppressed CAFs activation, and abrogated the promoting effect of CAFs on migration and invasion of non-small cell lung cancer cells (NSCLC), through attenuating CAFs’ effect on epithelial mesenchymal transition (EMT) process, metastasis-related genes (MMP9, TWIST1) and AKT/endothelial nitric oxide synthase (eNOS) signaling pathway. Further study indicated that vascular endothelial growth factor A (VEGFA) was a novel target of miR-101-3p, and CAFs-derived VEGFA mediated the effect of miR-101-3p on migration and invasion of lung cancer cells, demonstrated by using recombinant VEGFA and VEGFA neutralizing antibody. Interestingly, the analysis of the Cancer Genome Atlas (TCGA) database revealed that lung cancer tissues expressed lower level of miR-101-3p than non-cancerous tissues, and low/medium-expression of miR-101-3p was associated with poor overall survival (OS) rate. Moreover, the mouse xenograft experiment also showed that CAFs accelerated tumor growth whereas miR-101-3p diminished CAFs’ effect. These findings revealed a novel mechanism that CAFs facilitated lung cancer metastasis potential via miR-101-3p/VEGFA/AKT signaling pathway, suggesting miR-101-3p as a potential candidate for metastasis therapy.